Implementation of Blockchain Technology on Accounting Information System For Transaction Security and Data Reliability - Pratiwi, Ariesta Edriana; Ermaya, Husnah Nur Laela (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research discusses the impact of blockchain technology on accounting information systems, with a focus on transaction security and data reliability. Blockchain, as an innovation in the digital world, promises significant improvements in security, transparency, and decentralization. Despite offering potential benefits, the implementation of blockchain in accounting information systems is still limited, with challenges involving high costs, lack of regulations, and data security concerns. In Indonesia, limited resources and digital literacy are key factors in overcoming these limitations. This research uses a qualitative descriptive approach because it aims to gain a deeper understanding. The qualitative approach allows researchers to analyze data, understand contexts, and formulate meaning from the information found. Data sources in this study were obtained from primary sources such as interviews and secondary data obtained from document studies. Interviews were conducted with participants knowledgeable about implementing blockchain in accounting information systems. The data collection process identified that blockchain can improve transaction security and data reliability in accounting information systems. However, scalability and integration with existing infrastructure pose challenges. Digital literacy awareness and infrastructure preparedness are identified as key factors for the successful implementation of blockchain technology in the accounting context. This research is expected to provide insights and recommendations for the development of blockchain technology and accounting information systems in the future. The implications of this research are that by implementing blockchain technology in accounting information systems, it can improve the quality of accounting information in companies and increase the long-term value of the company.